The Distribution and Conservation Status of Green Turtles (Chelonia mydas) and Olive Ridley Turtles (Lepidochelys olivacea) on Pulau Pinang beaches (Malaysia), 1995–2009 - Sarahaizad Mohd Salleh; Mansor Yobe; Shahrul Anuar Mohd Sah (Tropical Life Sciences Research, 2012)
The Green Turtle (Chelonia mydas) and Olive Ridley Turtle (Lepidochelys olivacea) are the only sea turtles with recorded landings in the Pulau Pinang coastal area. The Green Turtle has been the most abundant and widely distributed sea turtle in this area since it was first surveyed in 1995. Statistical analysis by the Pulau Pinang Department of Fisheries on the distribution of sea turtles from 2001 through 2009 has identified Pantai Kerachut and Telok Kampi as the most strongly preferred beaches for Green Turtle landings, with records for almost every month in every year. Green Turtle tracks and nests have also been found along the coast of Pulau Pinang at Batu Ferringhi, Tanjong Bungah, Pantai Medan, Pantai Belanda, Telok Kumbar, Gertak Sanggul, Moonlight Beach, Telok Duyung, Telok Aling, Telok Bahang and Telok Katapang. The Olive Ridley Turtle is present in smaller numbers; landing and nesting have only been recorded on a few beaches. There are no previous records of Olive Ridley landings at Pantai Kerachut and Telok Kampi, but tracks and nests have been found at Telok Kumbar, Tanjong Bungah, Pantai Medan, Telok Duyung and Gertak Sanggul. A Turtle Conservation Centre has been established at Pantai Kerachut to protect these species from extinction in Pulau Pinang. This paper presents details of the records and distribution of sea turtles in Pulau Pinang from 1995 through 2009. Penyu agar atau penyu hijau (Chelonia mydas) dan penyu lipas (Lepidochelys olivacea) adalah dua spesies penyu yang direkodkan mendarat di perairan laut Pulau Pinang. Penyu agar mempunyai rekod pendaratan tertinggi di Pulau Pinang sejak tahun 1995. Daripada statistik pendaratan penyu yang dikeluarkan oleh Jabatan Perikanan Pulau Pinang dari tahun 2001 hingga 2009, Pantai Kerachut dan Telok Kampi telah disenaraikan sebagai lokasi dengan pendaratan tertinggi penyu agar dengan pendaratan pada hampir setiap bulan dan pada sepanjang tahun. Sarang dan trek pendaratan penyu agar dijumpai hampir di keseluruhan pantai di Pulau Pinang iaitu di Batu Ferringhi, Tanjong Bungah, Pantai Medan, Pantai Belanda, Telok Kumbar, Gertak Sanggul, Pantai Moonlight, Telok Duyung, Telok Aling dan Telok Katapang. Tiada rekod pendaratan penyu lipas di Pantai Kerachut and Telok Kampi, tetapi trek dan sarang dijumpai di Telok Kumbar, Tanjong Bungah, Pantai Medan, Telok Duyung dan Gertak Sanggul. Justeru, Pusat Konservasi Penyu ditubuhkan di Pantai Kerachut untuk melindungi spesies ini daripada terus diancam kepupusan. Kajian ini akan menbincangkan tentang rekod dan taburan penyu agar dan penyu lipas di Pulau Pinang dari tahun 1995 hingga 2009.